Targeting YY1-DR5 Axis by Pyripyropene O as a Novel Therapeutic Strategy Against Prostate Cancer: Molecular Mechanisms and In Vivo Zebrafish Validation - Wenxuan Fang; Ying Chen; Mingyi Nie; Xuefeng Zhou; Yonghong Liu; Huaming Tao; Bin Yang; Xueni Wang (Marine Drugs)
Background: Induction of apoptosis is an important strategy for the treatment of prostate cancer. DR5 is a member of the death receptor superfamily and targeting DR5 is an effective way to induce apoptosis. Pyripyropene O is a natural compound isolated from the marine fungus Aspergillus fumigatus SCSIO 41220. We found it has anti-prostate cancer potential by inducing apoptosis; Methods: The effects of pyripyropene O on the viability, proliferation, cell cycle, apoptosis and migration of prostate cancer cells were investigated by MTT assay, plate clone formation assay, 3D cell sphere assay, flow cytometry and real-time cell analysis. Transmission electron microscopy was used to observe the changes in the internal structure of prostate cancer cells after treatment with pyripyropene O. After determining the mode of cell death, the mechanism of action of pyripyropene O on prostate cancer was further investigated using apoptotic protein microarray, western blot, qPCR, molecular docking, cellular immunofluorescence staining and cellular thermal shift assay. After explaining the mechanism of action of pyriproxyfen O, the in vivo absorption, distribution, metabolism, excretion and potential toxicity of pyriproxyfen O were investigated using ADMETLab 2.0 software. Finally, a zebrafish xenograft tumour model was developed to evaluate the anti-prostate cancer effects of pyriproxyfen O in vivo; Results: The experimental results at the cellular level showed that pyripyropene O inhibited the survival, proliferation and migration of prostate cancer cells, and also showed that pyripyropene O blocked the prostate cancer cell cycle at the G2/M phase and induced apoptosis. At the molecular level, pyripyropene O binds to the transcription factor YY1, promotes YY1 nuclear translocation, regulates the transcription level of DR5, a target gene of YY1, and upregulates the expression of DR5 mRNA and protein. The in vivo results showed that pyripyropene O effectively inhibited the development of prostate cancer in zebrafish; Conclusions: Pyripyropene O has a clear anti-prostate cancer effect at both cellular and animal levels, inhibiting the survival and proliferation of prostate cancer cells by binding to the transcription factor YY1 to activate the expression of DR5 to promote apoptosis, thus exerting an inhibitory effect on prostate cancer.